Strategic Management of Digital Transformation: Prioritizing Initiatives Using AHP in Indonesia’s IT Sector - Akmal, Muhammad Hafizh (Jurnal Bisnis dan Pemasaran Digital, 2025)
Purpose: The rapid pace of digital transformation has significantly impacted the IT services sector, particularly in emerging markets, such as Indonesia. This thesis explores the strategic challenges faced by Indonesian IT service providers as they navigate a competitive landscape characterized by evolving customer demands, technological advancements, and market dynamics. This research aims to prioritize strategic initiatives that align with market needs and enhance the competitive positioning of these providers. Research Methodology: By integrating strategic management frameworks such as Porter’s Five Forces, Value Chain Analysis, and SWOT Analysis with the Analytic Hierarchy Process (AHP), this study addresses the issue of stagnant revenue in PT ABC, a leading IT service provider in Indonesia. The findings indicate that AI-based product innovation and the development of low-code solutions are critical strategies for driving sustainable growth and meeting the increasing demand for advanced technological solutions. Conclusions: PT ABC should prioritize AI-based product innovation to meet the growing market demand for advanced and easily integrated technological solutions. The development of low-code platforms is essential to enhance customization capabilities and accelerate delivery times, addressing customer expectations for scalability and efficiency. Market Demand & Growth Potential, along with Operational Efficiency & Scalability, are the key strategic criteria guiding PT ABC’s innovation and service enhancement priorities. Limitations: This study underscores the importance of customer-centric approaches and continuous adaptation to maintain a competitive edge in a volatile, uncertain, complex, and ambiguous (VUCA) environment. Contributions: This research contributes to the strategic management literature by demonstrating the practical application of AHP in the context of digital transformation within the IT services sector, and provides actionable insights for IT service providers in emerging markets facing similar challenges.